2019
DOI: 10.7150/thno.31844
|View full text |Cite
|
Sign up to set email alerts
|

AIE-based theranostic systems for detection and killing of pathogens

Abstract: Pathogenic bacteria, fungi and viruses pose serious threats to the human health under appropriate conditions. There are many rapid and sensitive approaches have been developed for identification and quantification of specific pathogens, but many challenges still exist. Culture/colony counting and polymerase chain reaction are the classical methods used for pathogen detection, but their operations are time-consuming and laborious. On the other hand, the emergence and rapid spread of multidrug-resistant pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 129 publications
(131 reference statements)
0
75
0
Order By: Relevance
“…[7] Therefore,d eveloping efficient non-cationic SNAc arrier with excellent lysosome escape capacity is highly desirable for gene delivery.Recent studies have demonstrated that photosensitizers (PSs) that are used clinically could produce large quantity of the reactive oxygen species (ROS) under light irradiation. [8] When PSs were taken up by cells and located in lysosomes,t he ROSp roduced by PSs could potentially rupture the membrane structure of lysosome and thus promote the cargo escape from there. [9] Tr aditional PSs generally show quenched fluorescence and compromised ROSg eneration in the aggregate state, which makes them less ideal for image-guided ROS production and photodynamic therapy (PDT).…”
Section: Introductionmentioning
confidence: 99%
“…[7] Therefore,d eveloping efficient non-cationic SNAc arrier with excellent lysosome escape capacity is highly desirable for gene delivery.Recent studies have demonstrated that photosensitizers (PSs) that are used clinically could produce large quantity of the reactive oxygen species (ROS) under light irradiation. [8] When PSs were taken up by cells and located in lysosomes,t he ROSp roduced by PSs could potentially rupture the membrane structure of lysosome and thus promote the cargo escape from there. [9] Tr aditional PSs generally show quenched fluorescence and compromised ROSg eneration in the aggregate state, which makes them less ideal for image-guided ROS production and photodynamic therapy (PDT).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that photosensitizers (PSs) that are used clinically could produce large quantity of the reactive oxygen species (ROS) under light irradiation. [8] When PSs were taken up by cells and located in lysosomes, the ROS produced by PSs could potentially rupture the membrane structure of lysosome and thus promote the cargo escape from there. [9] Traditional PSs generally show quenched fluorescence and compromised ROS generation in the aggregate state, which makes them less ideal for image-guided ROS production and photodynamic therapy (PDT).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, various AIE bioprobes have been designed: (i) water‐soluble AIEgens, which are comprised of a hydrophobic AIE core and hydrophilic units (e.g., ionic groups, peptides, carbohydrates, DNA, aptamers, antibodies, and poly(ethylene glycol) (PEG)); (ii) bare AIEgen dots (nanoaggregates); iii) AIEgen/biopolymer dots, which can be obtained by loading AIEgens onto biopolymer matrixes covalently (e.g., chitosan, dextran, and starch) or noncovalently (e.g., bovine serum albumin, human serum albumin (HSA), and fetal bovine serum (FBS)); (iv) AIEgen/silica dots, which can be prepared by physically encapsulating AIEgens into a silica shell; (v) AIEgen/polymer dots, which can be fabricated by physically encapsulating AIEgens within amphipathic polymers (e.g., 1,2‐distearoyl‐ sn ‐glycero‐3‐phosphoethanolamine‐ N ‐(polyethylene glycol) (DSPE‐PEG), and Pluronic F127); and (vi) polymer AIEgen dots, which are polymer dots that contain AIE units on the polymer backbone or side‐chains ( Figure A). Many applications of these bioprobes have been demonstrated in recent years, such as biosensing (including protein/enzyme, nucleic acid, carbohydrate, and amino acid), bioimaging (including subcellular, cellular, tissue, and small animal), pathogenic detection and killing, and disease theranostics . To offer a clear picture of research progress in AIE bioprobes, many comprehensive reviews have been previously published, which discussed and summarized AIE bioprobe structures,15c,h,17c,20 applications,15a,b,e‐g,17b,19a‐d,f,21 performance,15d,i,17a,19e,22 and working mechanisms 14,16,18,19g,23.…”
Section: Introductionmentioning
confidence: 99%
“…Many applications of these bioprobes have been demonstrated in recent years, such as biosensing (including protein/enzyme, nucleic acid, carbohydrate, and amino acid), bioimaging (including subcellular, cellular, tissue, and small animal), pathogenic detection and killing, and disease theranostics . To offer a clear picture of research progress in AIE bioprobes, many comprehensive reviews have been previously published, which discussed and summarized AIE bioprobe structures,15c,h,17c,20 applications,15a,b,e‐g,17b,19a‐d,f,21 performance,15d,i,17a,19e,22 and working mechanisms 14,16,18,19g,23. In light of the rapid development of AIE bioprobes, this review will primarily focus on recent advances in applying AIEgens in the field of small animal models (mouse, rat, and zebrafish).…”
Section: Introductionmentioning
confidence: 99%